Synthesis and Assessment of Antibacterial Activities of Ruthenium(III) Mixed Ligand Complexes Containing 1,10-Phenanthroline and Guanide - Atakilt Abebe; Tizazu Hailemariam (Bioinorganic Chemistry and Applications)
In this work, two complexes of ruthenium(III) ([Ru(phen)2Cl2]Cl·2H2O and [Ru(phen)2(G)Cl]2Cl·H2O) were synthesized from 1,10-phenanthroline alone as well as from both 1,10-phenanthroline and guanide. The synthesis was checked using halide test, conductance measurement, and spectroscopic (ICP-OES, FTIR, and UV/Vis) analysis. Their in vitro antibacterial activities were also investigated on two Gram-positive (Staphylococcus aureus (S. aureus) and methicillin resistant Staphylococcus aureus (MRSA)) and two Gram-negative (Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae)) bacteria. These complexes showed wide-range better activities than the commercially available controls (Chloramphenicol and Ciprofloxacin) against even the most drug resistant K. pneumoniae. [Ru(phen)2(G)Cl]2Cl·H2O inhibited S. aureus, MRSA, E. coli, and K. pneumoniae by 17.5%, 27.4%, 16%, and 52%, respectively, better than Chloramphenicol. It also inhibited these pathogens by 5.9%, 5.1%, 2.3%, and 17.2%, respectively, better than Ciprofloxacin. Similarly, [Ru(Phen)2(Cl)2]Cl·2H2O inhibited these pathogens by 11%, 8.7%, 0.1%, and 31.2%, respectively, better than Chloramphenicol. Therefore, after in vivo cytotoxicity investigations, these compounds can be considered as potential antibiotic drugs.